2012
DOI: 10.2119/molmed.2011.00461
|View full text |Cite
|
Sign up to set email alerts
|

Implication of AMP-Activated Protein Kinase in Transient Receptor Potential Vanilloid Type 1-Mediated Activation of Endothelial Nitric Oxide Synthase

Abstract: We investigated whether AMP-activated protein kinase (AMPK), a multifunctional regulator of energy homeostasis, is involved in transient receptor potential vanilloid type 1 (TRPV1)-mediated activation of endothelial nitric oxide synthase (eNOS) in endothelial cells (ECs) and mice. In ECs, treatment with evodiamine, the activator of TRPV1, increased the phosphorylation of AMPK, acetyl-CoA carboxylase (ACC) and eNOS, as revealed by Western blot analysis. Inhibition of AMPK activation by compound C or dominant-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 50 publications
2
52
0
Order By: Relevance
“…Therefore, AMPK is now considered to be a potential pharmacologic target for improving insulin resistance, diabetes and metabolic syndrome. Ching et al have recently reported that evodiamine increased AMPK phosphorylation in endothelial cells [34]. In the present study, we found that evodiame significantly stimulated AMPK phosphorylation in mature adipocyte culture and in WAT of KK-Ay mice.…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, AMPK is now considered to be a potential pharmacologic target for improving insulin resistance, diabetes and metabolic syndrome. Ching et al have recently reported that evodiamine increased AMPK phosphorylation in endothelial cells [34]. In the present study, we found that evodiame significantly stimulated AMPK phosphorylation in mature adipocyte culture and in WAT of KK-Ay mice.…”
Section: Discussionsupporting
confidence: 76%
“…For example, phosphorylation of eNOS at both Ser1177 and Ser633 in human endothelial cells (Ser1179 and Ser635 in mouse ECs) by PI3K/Akt, calmodulin-dependent protein kinase and AMP-activated protein kinase increases eNOS activity. By the contrast, phosphorylation of eNOS at Thr495 in human ECs (Thr497 in mouse ECs) by protein kinase C decreases eNOS activity (Arnal et al 1999;Venema 2002;Mount et al 2007;Ching et al 2011Ching et al , 2012Ching et al , 2013Su et al 2012Su et al , 2014. Impaired eNOS activity is an important event in the development of cardiovascular diseases such as hypertension (Davignon and Ganz 2004;Vanhoutte et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, TRPV1 activation by capsaicin increased the activity of endothelial NO synthase (eNOS), promoted vasorelaxation, and thereby reduced blood pressure in experimental hypertensive rats [25]. Additionally, we previously reported that TRPV1 activation by evodiamine or capsaicin triggered Ca 2+ -dependent PI3 K/Akt/CaMKII/AMPK signaling, thus leading to eNOS activation in ECs [27, 56]. As well, inactivation of TRPV1 accelerates the development of metabolic disorders such as hypertension, atherosclerosis, obesity, and fatty liver, whereas TRPV1 agonist activation protects against these metabolic diseases [25, 55, 57, 58].…”
Section: Discussionmentioning
confidence: 99%